The relationship between hope, medical expenditure and survival among advanced cancer patients - Chay, Junxing; Huynh, Vinh Anh; Cheung, Yin Bun; Kanesvaran, Ravindran; Lee, Lai Heng; Malhotra, Chetna; Finkelstein, Eric Andrew (Frontiers in Psychology, 2023)
Introduction Among those with advanced illness, higher levels of hope may offer physiological benefits. Yet, greater levels of hope may also encourage aggressive treatments. Therefore, higher levels of hope may lead to greater healthcare utilization, higher expenditure, and longer survival. We test these hypotheses among patients with advanced cancer. Methods A secondary data analysis from a cross-sectional survey of 195 advanced cancer patients with high mortality risk linked to subsequent healthcare utilization (outpatient, day surgeries, non-emergency admissions), health expenditures, and death records. The survey collected data on hope, measured generally by the Herth Hope Index (HHI) and more narrowly by two questions on illness-related hope. Generalized linear regression and Cox models were used to test our hypotheses. Results 142 (78%) survey participants died during the period of analysis, with close to half (46%) doing so within a year of the survey. Contrary to expectation, HHI scores did not have a significant association with healthcare utilization, expenditure or survival. Yet, illness-related hope, defined as those who expected to live at least 2 years, as opposed to the likely prognosis of 1 year or less as determined by the primary treating oncologist, had 6.6 more planned hospital encounters (95% CI 0.90 to 12.30) in the 12-months following the survey and 41% lower mortality risk (hazard ratio: 0.59, 95% CI 0.36 to 0.99) compared to those who were less optimistic. Secondary analysis among decedents showed that patients who believed that the primary intent of their treatment is curative, had higher total expenditure (S$30,712; 95% CI S$3,143 to S$58,282) in the last 12 months of life than those who did not have this belief. Conclusion We find no evidence of a relationship between a general measure of hope and healthcare utilization, expenditure, or survival among advanced cancer patients. However, greater illness-related hope is positively associated with these outcomes.